Overview of Alternative Sanctions and Programs in Work with Sexual Assault Perpetrators - Ćumura, Ljiljana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
Any form of violence, especially sexual abuse of minors, is rightly referred to as the most difficult aspect of domestic violence and violence in general. Although the public is, through media, familiar with the widespread of sexual abuse and exploitation of children, we cannot say that there is an interest in deeper and more detailed work on these issues and the factors that cause this type of behavior. Especially, seeking and searching for different types of treatment and support for sexual abusers, in order to change their personality and protect potential future victims. One gets the impression that the public continues to show strong dissatisfaction with the proposed legal solutions, while expressing the need for a new and even more radical approach. However, the new legislation allows, among other things, the implementation of alternative sanctions and measures of restorative character, which have already been applied in the world for decades. The author analyzes different types of therapy and restorative approaches for perpetrators of sexual offenses, emphasizing that public awareness of the nature and importance of alternative methods of treatment and rehabilitation is still not sufficiently developed, and that the finding of equitable legislative solutions for perpetrators of sexual offenses is not at all a simple or easy task.